Does Economic Policy Uncertainty Affect Foreign Remittances? Linear and Non-linear ARDL Approach in BRIC Economies - Rana Yassir Hussain; Namarta Kumari Bajaj; Sonia Kumari; Mamdouh Abdulaziz Saleh Al-Faryan (Cogent Economics & Finance, 2023)
This study investigates the impact of economic policy uncertainty (EPU) on foreign remittances and whether it affects them symmetrically or asymmetrically. The ARDL model is employed to examine the short-run and long-run symmetric impact of EPU on foreign remittances, while the NARDL model is utilized to examine the short-run and long-run asymmetric impact of EPU on foreign remittances, using monthly data for the BRIC economies (Brazil, Russia, India, and China). The results indicate that in the short-run, EPU has a positive and significant impact only on the inflows of foreign remittances received in Russia. Additionally, the short-run asymmetric impact of EPU on foreign remittances is found in Russia and India. Meanwhile, the long-run asymmetric impact of EPU on foreign remittances is observed in the BRIC economies. In particular, the results show that the non-linear response of EPU varies among the sampled countries. The findings of this study enhance our understanding of the role of policy uncertainty in overseas remittances. This information would be beneficial for policymakers, migrants, and recipients, as they are directly involved in making decisions about policies and the transfer of remittances, respectively.
Keywords: A10; C13; G28; 330; Economic policy uncertainty; foreign remittances; NARDL